Quantitation of intracellular NAD(P)H can monitor an imbalance of DNA single strand break repair in base excision repair deficient cells in real time - Nakamura, Jun (Oxford University Press, 2003)
DNA single strand breaks (SSBs) are one of the most frequent DNA lesions in genomic DNA generated either by oxidative stress or during the base excision repair pathways. Here we established a new real-time assay to assess an imbalance of DNA SSB repair by indirectly measuring PARP-1 activation through the depletion of intracellular NAD(P)H. A water-soluble tetrazolium salt is used to monitor the amount of NAD(P)H in living cells through its reduction to a yellow colored water-soluble formazan dye. While this assay is not a direct method, it does not require DNA extraction or alkaline treatment, both of which could potentially cause an artifactual induction of SSBs. In addition, it takes only 4 h and requires less than a half million cells to perform this measurement. Using this assay, we demonstrated that the dose- and time-dependent depletion of NAD(P)H in XRCC1-deficient CHO cells exposed to methyl methanesulfonate. This decrease was almost completely blocked by a PARP inhibitor. Furthermore, methyl methanesulfonate reduced NAD(P)H in PARP-1(+/+)cells, whereas PARP-1(–/–) cells were more resistant to the decrease in NAD(P)H. These results indicate that the analysis of intracellular NAD(P)H level using water-soluble tetrazolium salt can assess an imbalance of SSB repair in living cells in real time.